Patriotic Anthem First of May - Carvajal Araya, María Isabel (2014)
Many where the elaborations that the liberal government towards the end of the 19th Century assumed to reinforce the nation’s imaginary. Among these strategies are the national anthems, which are depositaries of the liberal ideals of the First Republic. This article inquires on this intangible monument, a forgotten part of the history of Costa Rica, a history which has been search and founded through different signs other than musical. With this work, in which the literal and musical analysis are intertwined, it is pretended to contribute, in however measure, to continue unraveling the chain of events and signs which constitute the patriotic history